2010
DOI: 10.1007/s00404-010-1355-y
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroids: risk of recurrence after myomectomy in a Nigerian population

Abstract: There is a high recurrence of uterine fibroid after myomectomy in our environment. The risk is higher among women with positive family history, multiple uterine fibroids, and in those with multiple symptoms. Pregnancy and use of OCP are protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
2
7
2
1
Order By: Relevance
“…Only 3.1% had recurrence during the follow-up period, which is much lower than 20.7% reported earlier in the same center among all patients 20. This is because of the decline in ovarian function toward the later part of the reproductive age and the consequent hypoestrogenic state that ensues.…”
Section: Discussionmentioning
confidence: 54%
“…Only 3.1% had recurrence during the follow-up period, which is much lower than 20.7% reported earlier in the same center among all patients 20. This is because of the decline in ovarian function toward the later part of the reproductive age and the consequent hypoestrogenic state that ensues.…”
Section: Discussionmentioning
confidence: 54%
“…Nishiyama et al [6] reported an increased risk of recurrence among patients with four or more leiomyomas [6]. Another study found that the risk of recurrence after multiple myomectomies was increased by 3.14‐fold [13]. This relationship might be explained by the surgical difficulty experienced in the removal of multiple leiomyomas or it could be a result of increased potential of the myometrium to produce leiomyoma [4].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies clearly defined the relationship between the number of leiomyomas removed and recurrence rates [6,7,9,12,13]. Two studies reported lowered recurrence rates after myomectomy among patients with one leiomyoma [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that recurrence of multiple uterine leiomyomas (MUL) occurs at higher rates than solitary uterine leiomyoma (SUL) (2)(3)(4). Moreover, clinical observation and epidemiology showed that SUL tended to grow in a larger diameter and rarely developed into multiple tumours.…”
Section: Introductionmentioning
confidence: 99%